High serum level of endostatin in multiple myeloma at diagnosis but not in the plateau phase after treatment - Halina Urbanska-Rys; Tadeusz Robak (Mediators of Inflammation)
We investigated the serum concentration of endostatin in 84 patients with multiple myeloma (MM) and in 13 healthy controls. The level of measured anti-angiogenic agent was correlated with the phase and stage of the disease, and most importantly with clinical and laboratory parameters depicting the disease activity (haemoglobin, creatinine, albumins, calcium, M-component, C-reactive protein, β2-microglobulin, lactate dehydrogenase, stage of bone disease) as well as serum levels of pro-angiogenic cytokines such as vascular endothelial growth factor, hepatocyte growth factor, fibroblast growth factor and transforming growth factor-β. The median serum level of endostatin in MM patients was 58 ng/ml and was statistically significantly higher than in the control group (median, 40 ng/ml; P=0.015). MM patients in phase I (at diagnosis) had higher levels of endostatin (median, 69 ng/ml) than those in phase II (plateau phase after treatment) (median, 49 pg/ml; P=0.044). We did not find any statistical correlation between the level of endostatin and stage of MM according to the Durie and Salmon system. The serum concentration of endostatin in MM patients with a normal level of albumins was significantly higher than in others with hypoalbuminaemia (median, 62 ng/ml versus 39 ng/ml; P=0.033). Also, patients with a normal value of lactate dehydrogenase had a higher concentration of endostatin than those with values >425 U/l (median, 70 ng/ml versus 39 ng/ml; P=0.019). We did not show any statistical correlation between the concentration of endostatin and level of haemoglobin, creatinine, calcium, C-reactive protein, β2-microglobulin and stage of bone disease. We failed to find positive or negative correlations between the level of endostatin and vascular endothelial growth factor, hepatocyte growth factor, fibroblast growth factor and transforming growth factor-β. The concentration of endostatin did not influence the probability of survival in MM patients in our study.